ANALISIS PERSEDIAAN BAHAN BAKU KAIN DENIM GRAMASI 10 OZ MENGGUNAKAN METODE PROBABILISTIK SEDERHANA DI PT XYZ - Aa Mustofa Sugiatna; Muhammad Iqbal Alkindi; Muchammad Fauzi (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2022)
Pandemic Covid-19 affected world economic that have correlation with the fluctuative of child denim fashion industry demand in 2020. The supply of raw materials in the warehouse is closely related to the needs of production process in the textile industry. Shortages or lack of supply of raw material can cause delays in the production process, it will cause the product cannot be delivered to the customer and lost of profit opportunity. Conversely, excessive stock can decrease profit of business because it can increase purchasing cost, ordering cost and holding cost. Optimization (Efficiency) is one of solution to control between demand and raw material balance. The purposes of this study are to find out how to optimize inventory of Economic Order Quantity, how much total cost of inventory per year, and Reorder point for denim 10 oz cotton-non-stretch raw material. The method of this study is simple probabilistic EOQ method. The result of Economic Order Quantity is 11.231 yard/order. Based on calculation, safety stock of denim 10 oz cotton-non-stretch material is 228 yard and re-order point is 1.126 yard